An analysis of the re-densification process in bogotá, an alternative for a sustainable urban growh? (2004)
At the interior of the contemporary urban discussion, subjects like city growth, and policies or strategies to deal with it, appear. Usually, densification of existent urban structures has raised as an alternative solution. However, the analysis of the methods and the specific urban conditions of each case, it means, the cities real condition, has been absent of the projects. Then, it emerges a disconnection between the theoretical discourse and the real tendencies. The present thesis undertook simultaneously a view to theoretic discourse and a constructed reality for the Bogotá case. Its results look forward to call the attention about the big inequities hidden by the figures, about how questionable results to insist in a discussion of expansion or densification, without involving both complexity and indicators.